Desenvolvimento de uma rota de processo de dessulfurização de rejeitos de um minério aurífero sulfetado - Getúlio Gomes de Oliveira Júnior (2011)
Since the beginning of its operation in 1987 until the late 90's, Kinross-Paracatu processed almost exclusively weathered or oxidized ores. Ores which are located bellow the B1 ore, containing sulfides and are called B2. They are characterized by sulphur content above 0.5%. The main sulphides are Arsenopyrite and Pyrite, occurring also traces of Galena, Sphalerite and chalcopyrite. Due the presence of sulphides, there is significant potential to generate acid, so it is necessary to generate a flotation tails with low sulphur content to reduce the potential of acid generation. The objective is to develop an alternative and safety route and for desulfurization, i.e., increase the recovery of sulphur present in a sulphide gold ore, thereby reducing their environmental impacts. The recoveries of sulphur using the current collectors, AP 3473 and AP 7249A, are in the range of 10%, being necessary to add lime to neutralize the acid generation in tailings dam and consequently increasing the costs operation. Was identified several conditions that promote desulfurization reagents without affecting the recovery of gold. Among the options evaluated in this work, it's possible affirm that the most interesting on several viewpoints, including economic, financial, and operational simplicity was the process of selective flotation, and in this case, it's possible use the current circuit of rougher and cleaner flotation at Kinross-Paracatu, requiring the addition of flotation cells for the stage of recleaner of sulfides.